Education of Autis Students at Islamic Boarding School Al Achsanyah - Partono Partono; Dindin Jamaludin; Muhamad Riza Chamadi; Salis Irvan Fuadi (EDUKASIA, 2021)
The purpose of the study was to find out how the educational process with autistic students intervention services at the Al-Achsaniyyah Kudus Islamic Islamic Boarding School. This research is a type of qualitative research with data analysis model of Miles and Huberman, data collection, data reduction, data presentation, and data verification. Data obtained through the process of interviews, observation, and documentation. The results of this study indicate that the educational model of Al-Achsaniyyah  Kudus Islamic Islamic Boarding School is different from other Islamic boarding schools. Kyai/ Caregiver at Al-Achsaniyyah  Kudus Islamic Islamic Boarding Schoolis not only a religious expert but also a doctor, Santri are children with autism syndrome. Al-Achsaniyyah Islamic Islamic Boarding School is not only a shelter but also a place of treatment and madrasa for autistic students. While the intervention service uses intervention services from an early age with the principle of Applied Behavior Analysis (ABA) on autistic students.